2016
DOI: 10.1186/s13568-016-0297-6
|View full text |Cite
|
Sign up to set email alerts
|

Halogenated indoles eradicate bacterial persister cells and biofilms

Abstract: The emergence of antibiotic resistance has necessitated new therapeutic approaches to combat recalcitrant bacterial infections. Persister cells, often found in biofilms, are metabolically dormant, and thus, are highly tolerant to all traditional antibiotics and represent a major drug resistance mechanism. In the present study, 36 diverse indole derivatives were investigated with the aim of identifying novel compounds that inhibit persisters and biofilm formation by Gram-negative Escherichia coli and Gram-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 40 publications
1
93
1
3
Order By: Relevance
“…Furthermore, substituted indoles reduce persistence (Lee et al, 2016). By testing 36 diverse indole derivatives for the ability to inhibit persister cells of Gram-negative E. coli and Gram-positive S. aureus , 5-iodoindole, 4-fluoroindole, 7-chloroindole, and 7-bromoindole were identified that eradicate persister cell formation by both bacteria.…”
Section: Reveiwmentioning
confidence: 99%
“…Furthermore, substituted indoles reduce persistence (Lee et al, 2016). By testing 36 diverse indole derivatives for the ability to inhibit persister cells of Gram-negative E. coli and Gram-positive S. aureus , 5-iodoindole, 4-fluoroindole, 7-chloroindole, and 7-bromoindole were identified that eradicate persister cell formation by both bacteria.…”
Section: Reveiwmentioning
confidence: 99%
“…In Pseudomonas putida , signalling molecules such as indole enhances TtgGHI efflux pump that are relevant for antibiotic resistance (Molina‐Santiago et al ., 2014). The previous studies have reported that indole inhibits biofilm formation and suppresses the virulence of bacterial strains such as Staphylococcus aureus , Agrobacterium tumefaciens (Lee and Lee, 2010; Lee et al ., 2013, 2015a,b; Lee et al ., 2016) and Vibrio cholera (Mueller et al ., 2009). Likewise, indole derivatives such as 7‐fluoroindole, 7‐hydroxyindole, 3‐indolyl acetonitrile and 2‐aminobenzimidazoles have been reported to exhibit antimicrobial activities against pathogenic bacteria (Lee et al ., 2009, 2011, 2012, 2015a,b; Frei et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…) and substituted indoles (Lee et al . ) have been shown to kill E. coli persister cells; however, they do not kill P. aeruginosa persisters (Lee et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…) have been shown to kill E. coli persister cells; however, they do not kill P. aeruginosa persisters (Lee et al . ). Critically, the effect of indole on persister cell waking has not been investigated previously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation